Legal Review of The Doctrine of Undue Influence (Abuse of Circumstances) in E-Commerce Agreements with Standard Clauses - Mega Arum Saputri; Agus Prasetia Wiranto (Jurnal Hukum Khaira Ummah, 2026)
This study aims to analyze the application of the doctrine of undue influence or abuse of circumstances (misbruik van omstandigheden) in e-commerce agreements that use standard clauses as the primary instrument of legal relations between business actors and consumers in the digital era. The development of electronic transactions has encouraged the use of standard clauses for efficiency, speed, and standardization of services, but on the other hand, raises serious issues related to consumer protection. Standard clauses in digital platforms often place consumers in a "take it or leave it" position, creating an imbalance in bargaining power, thus opening up opportunities for exploitation by dominant parties. In these conditions, consumers often do not have adequate opportunities to understand, negotiate, or reject the contents of the agreement due to limited information, urgent needs, or dependence on certain digital services. This study uses a normative juridical method with a statutory and conceptual approach to examine positive legal norms and relevant contract law doctrines. The results show that the element of abuse of circumstances, both economic and psychological, can be fulfilled when business actors exploit their dominant position to establish clauses that are disproportionate and detrimental to consumers. This practice demonstrates that standard clauses in e-commerce do not always reflect contractual fairness, but instead can reinforce the dominance of business actors. Therefore, while standard clauses are permitted in modern business practices, their application must be limited by the principles of good faith, balance, and protection of the weaker party to prevent them from becoming a means of abuse, leading to contractual unfairness and a decline in trust in the digital ecosystem.